The population approach to falls injury prevention in older people: findings of a two community trial - Dietrich Uta; McKenzie Kirsten; Ren Cizao; Hughes Karen; McClure Rod J; Vardon Paul; Davis Elizabeth; Newman Beth (BMC, 2010)
Abstract Background There is a sound rationale for the population-based approach to falls injury prevention but there is currently insufficient evidence to advise governments and communities on how they can use population-based strategies to achieve desired reductions in the burden of falls-related injury. The aim of the study was to quantify the effectiveness of a streamlined (and thus potentially sustainable and cost-effective), population-based, multi-factorial falls injury prevention program for people over 60 years of age. Methods Population-based falls-prevention interventions were conducted at two geographically-defined and separate Australian sites: Wide Bay, Queensland, and Northern Rivers, NSW. Changes in the prevalence of key risk factors and changes in rates of injury outcomes within each community were compared before and after program implementation and changes in rates of injury outcomes in each community were also compared with the rates in their respective States. Results The interventions in neither community substantially decreased the rate of falls-related injury among people aged 60 years or older, although there was some evidence of reductions in occurrence of multiple falls reported by women. In addition, there was some indication of improvements in fall-related risk factors, but the magnitudes were generally modest. Conclusions The evidence suggests that low intensity population-based falls prevention programs may not be as effective as those that are intensively implemented.